Health Conditions and Psychotic Experiences: Cross-Sectional Findings From the American Life Panel - Oh, Hans; Smith, Lee; Koyanagi, Ai (Frontiers in Psychiatry, 2021)
Background: People with psychotic disorders have poor health, but studies have shown that people who have a milder and more prevalent form of psychosis (psychotic experiences) are also at risk for health problems. More research is needed to examine a broad range of health conditions to discover new relations with psychotic experiences. Methods: We analyzed cross-sectional data from the American Life Panel, a nationally representative sample of the United States adult population. Using multivariable logistic regression, we examined the associations between health conditions (categories of conditions, specific conditions, count of conditions) and lifetime psychotic experiences. Results: Approximately 71% of the weighted sample reported at least one health condition, and around 18% reported a lifetime psychotic experience. Using multivariable logistic regression, we found that several health conditions were associated with psychotic experiences, including pain due to other causes, neck pain, other injury, any gastrointestinal/kidney problem, liver diseases/cirrhosis, any nervous/sensory problem, migraine, nerve problem causing numbness/pain, any other disorder, specifically sleep disorder, chronic fatigue syndrome, and chronic pain. Further, the count of specific health conditions and the count of categories were associated with greater odds of psychotic experiences . Conclusion: We found that numerous health conditions were associated with psychotic experiences.